Bibliometric study of immunotherapy for hepatocellular carcinoma - Li, Zhiyi; Zhang, Ying; Zhang, Baipan; Guo, Rui; He, Minhua; Liu, Zi-Ling; Yang, Lei; Wang, Hong (Frontiers in Immunology, 2023)
Background Hepatocellular carcinoma (HCC), recognized as a significant global health concern, ranks as the sixth most prevalent form of cancer and is the third leading cause of cancer-associated mortality. Over half of HCC patients are diagnosed at advanced stages, an unfortunate phenomenon primarily attributed to the liver’s robust compensatory mechanisms. Given the limited availability of donor livers, existing clinical surgical approaches have yet to provide universally applicable treatment strategies offering substantial prognostic improvement for late-stage cancer. Although the past few decades have witnessed significant advancements in chemotherapy and targeted therapy for HCC, the emergence of drug resistance poses a substantial impediment to their successful execution. Furthermore, issues such as diminished quality of life post-treatment and high treatment costs warrant critical attention. Consequently, the imperative for an effective treatment strategy for advanced liver cancer is unequivocal. In recent years, notable progress in the development and application of immunotherapy has sparked a revolution in advanced liver cancer treatment. This study aims to elucidate a more comprehensive understanding of the current landscape, knowledge framework, research focal points, and nascent breakthrough trends in the domain of immunotherapy for hepatocellular carcinoma via bibliometric analysis. Method Our study involved conducting a comprehensive literature search spanning from 1999 through December 31, 2022, by utilizing the Science Citation Index Expanded (SCI-Expanded) database. Our aim was to amass all the papers and reviews related to immunotherapy for hepatocellular carcinoma. Our search strategy yielded a total of 4,486 papers. After exclusion of self-citations, we focused our analysis on 68,925 references. These references were cited 119,523 times (excluding 97,941 self-citations), boasting an average citation frequency of 26.64 times per paper, and achieved an h-index of 135. We employed analytical software tools like Citespace and VOSviewer to perform an intricate analysis of the amassed literature, covering various aspects, including geographical location, research institutions, publishing journals, authors, references, and keywords. Our method incorporated timeline analysis, burst detection, and co-occurrence analysis. The application of these tools facilitated a thorough evaluation of research hotspots, knowledge structure, and emerging advancements within the sphere of immunotherapy for hepatocellular carcinoma. Results Our bibliometric analysis disclosed a noteworthy escalation in the number of publications in the realm of hepatocellular carcinoma immunotherapy during the years 2021-2022, surpassing the aggregate number of papers published in the preceding decade (2011–2020). This surge underscores a sharp upturn in research interest within this field. Additionally, the research hotspot in hepatocellular carcinoma immunotherapy has perceptibly deviated from the preceding decade’s trends. In terms of geographical distribution, China emerged as the leading country, producing 50.08% of the total publications. This was followed by the United States, with 963 papers, and Japan, contributing 335 papers. Among research institutions, Sun Yat-sen University was the most prolific, while Tim F. Greten stood out as the most published author with 42 papers to his credit. A co-reference network examination uncovered a shift in research emphasis within the field of hepatocellular carcinoma immunotherapy, highlighting the evolving nature of this important area of study Conclusion Our bibliometric study highlights the significant evolution and growth in HCC immunotherapy research over the past two decades. Looking ahead, research will focus on improving the microenvironment post-drug resistance from immune combination therapy, harnessing adoptive cellular immunity (as CAR-T), subclassify the population and developing new tumor markers. Incorporation of technologies such as nanotechnology, microbiology, and gene editing will further advance HCC treatments. This progressive trajectory in the field promises a brighter future for individuals suffering from HCC.